Odpowiedzi

2009-11-12T21:06:05+01:00
Y=-x-7
-y=-x²+x+7,25

y=-x-7
-(x-7)=-x²+x+7,25

y=-x-7
x+7=-x²+x+7,25

y=-x-7
x+x²-x=7,25-7

y=-x-7
x²=0,25

y=-x-7
x=0,5 ∨ x=-0,5

y=-0,5-7 y=0,5-7
x=0,5 x=-0,5

y=-7,5 y=-6,5
x=0,5 x=-0,5
2009-11-12T21:07:18+01:00
Y=-x-7
-y=-x²+x+7,25 /*-1

y=-x-7
y=x²-x-7¼

-x-7=x²-x-7¼

x²-x+x-7¼+7=0

x²-¼=)

Δ=-4*1*(-¼)
Δ=1
x₁=o-1/2=-½
x₂=o+1/2=½

y₁=-½-7=-7½
y²=½-7=-6½


chyba dobrze jak się nie pomyliłam w obliczeniach:D pozdrawiam

2009-11-12T21:11:23+01:00
Y=-x-7
-y=-x²+x+7,25

y=-x-7
-(x-7)=-x²+x+7,25

y=-x-7
x+7=-x²+x+7,25

y=-x-7
x+x²-x=7,25-7

y=-x-7
x²=0,25

y=-x-7
x=0,5

y=-0,5-7
x=0,5

y=-7,5
x=0,5